Depth effects of long-term organic residue application on soil organic carbon stocks in central Kenya - Müller, Claude Raoul; Six, Johan; Njiru, Daniel Mugendi; Vanlauwe, Bernard; Broek, Marijn Van de (UoEm, 2025)
In arable soils, a substantial portion of soil organic carbon (SOC) is stored below the plough layer. To develop sustainable soil management strategies, it is important to assess how they affect the quantity of SOC stored in the subsoil. Therefore, we investigated the impact of organic and inorganic nutrient inputs on SOC stocks down to 70 cm depth in a long-term field trial in Embu, Kenya. There were three organic input treatments (manure, Tithonia diversifolia residues, and maize stover) and a control treatment, each with and without the application of mineral nitrogen. These different treatments were applied to a maize monoculture over 38 growing seasons (19 years). Our results show that manure application had the largest positive impact on SOC stocks compared to the control; this effect was observed down to 60 cm depth. In contrast, Tithonia diversifolia and maize stover application led to significantly larger SOC stocks compared to the control, although this was only within the top 20 cm and 40 cm, respectively. Among the three organic residue treatments, only the application of manure had a significant effect on the SOC stock of the subsoil (i.e. the 30–70 cm depth layer). However, when considering the whole measured profile (i.e. 0–70 cm), all treatments led to significantly higher SOC stocks compared to the 91 ± 12 t C ha−1 of the control: manure had the highest stocks (120 ± 24 t C ha−1), followed by maize stover (112 ± 17 t C ha−1) and Tithonia diversifolia (105 ± 11 t C ha−1). Mineral nitrogen application did not have a significant impact on SOC stocks down to 70 cm depth. Our findings demonstrate that SOC in the subsoil comprised 48.5 % ± 1.7 % of the total SOC stocks across the 0–70 cm soil profile; however, only manure application affected subsoil OC levels, whereas other organic amendments solely increased SOC in the surface layer. Our results imply that gathering knowledge on the soil below the typically studied 0–30 cm depth layer will improve the overall assessment of agroecosystem properties, which is necessary to optimize soil system resilience, limit organic matter losses, and improve crop productivity.
Article
Keywords: soil organic